The Orphan : A Cinderella Story from Greece - Manna, Anthony L.; Mitakidou, Christodoula; Potter, Giselle (New York : Schwartz & Wade Books, 2011)
In this variation on the Cinderella story set in Greece, a girl mistreated by her stepmother and stepsisters manages to captivate the prince, with help from Mother Nature and her children.
Keywords: Fairy tales; Folklore